Behavioral Inhibition: Linking Biology and Behavior within a Developmental Framework - Fox, Nathan A.; Henderson, Heather A.; Marshall, Peter J.; Nichols, Kate E.; Ghera, Melissa M. (Annual review of psychology, 2005)
Behavioral inhibition refers to a temperament or style of reacting that some infants and young children exhibit when confronted with novel situations or unfamiliar adults or peers. Research on behavioral inhibition has examined the link between this set of behaviors to the neural systems involved in the experience and expression of fear. There are strong parallels between the physiology of behaviorally inhibited children and the activation of physiological systems associated with conditioned and unconditioned fear. Research has examined which caregiving behaviors support the frequency of behavioral inhibition across development, and work on the interface of cognitive processes and behavioral inhibition reveal both how certain cognitive processes moderate behavioral inhibition and how this temperament affects the development of cognition. This research has taken place within a context of the possibility that stable behavioral inhibition may be a risk factor for psychopathology, particularly anxiety disorders in older children. The current chapter reviews these areas of research and provides an integrative account of the broad impact of behavioral inhibition research.